Stand by me : a guide to navigating modern, meaningful caregiving - Applebaum, Allison (Simon Element, 2024)
"Compassionate, groundbreaking, and urgently needed, Stand By Me provides caregivers with new ways to juggle the responsibilities and emotional ups and downs of caregiving. As the founder of the only devoted Caregivers Clinic in the country, clinical psychologist Dr. Allison Applebaum is no stranger to the intensity of being an unpaid, untrained family caregiver. She also understands that it is often the strength and well-being of these very caregivers-the parents, children, partners, siblings, and friends of patients-that are the true linchpin determining each patient's illness experience. This book puts the practical tools and transformative support of the Caregivers Clinic in your hands, empowering you to provide your loved one with the best quality of life and care possible, while promoting your own wellbeing. The book covers crucial topics including: -Getting the most from any healthcare system -Productive advance care planning -Navigating changing roles and relationship dynamics -Finding meaning and purpose in the caregiving experience Stand By Me draws on a decade of clinical and research experience as well as Dr. Applebaum's personal journey as the primary caregiver for her own father, legendary composer Stanley Applebaum, at the end of his life. Dr. Applebaum recognizes caregivers for who they truly are: invaluable healthcare team members. Offering critical insight and takeaways, Stand By Me is an essential resource throughout your caregiving journey"--